“DOCTOR! Go for a course in HR Management” - S.A.H. Moosa; I.D. Couper (South African Family Practice)
A key principle of family medicine is the management of resources. Human Resource Management (HRM) underpins other principles of family medicine. It is not only the doctor but also the staff around him or her who enables and responds to the patient experience. South African private general practitioners struggle with staff management within an increasingly complex and regulated environment. Simple approaches, documents such as employment contracts and codes of conduct, and checklists highlighting statutory and best practise requirements can ensure good HRM. People-centred HRM contributes to a patient-centred practice. It can also address skills and incapacity in a fair manner, keeping the practice within the law and partnering in social transformation and primary health care delive